MODELLING OF EXTERNAL FIRE PROTECTION WATER SUPPLY SOURCES IN THE SUBSTANTIATION OF SPECIAL TECHNICAL CONDITIONS - O. I. Stepanov; S. A. Khudyakova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives This paper sets out to provide a theoretical substantiation of the placement of external fire-prevention water supply sources when designing unique construction objects, for which standard requirements of fire safety cannot be applied. Problematic situations arising during the design of unique construction objects, which relate to the provision of the required level of fireextinguishing substances supply, are described.Method A model constructed on the basis of graph theory is presented for the preliminary calculation of the location of external fire-fighting water supply sources that takes the equipment of fire-rescue units into account. The utility of developing a universal mathematical model for the preliminary definition of arrangement parameters of sources of external fire-prevention water supply when designing construction objects is substantiated.Results Examples of preliminary calculation of the number of external fire-fighting water supply sources are given considering the shape of the building perimeter. Additional factors determining the distances from external fire-fighting water supply sources to the projected objects are given.Conclusion A conclusion regarding the adequacy of the proposed model is formulated and directions for future research indicated that allows the applicability of the model to be specified for the calculation of the projected objects, which differ in terms of dimensions given in the plan by above-normative characteristics.